Characterisation of chitosan solubilised in aqueous formic and acetic acids - El-hefian, E.A.; Yahaya, A.H.; Misran, M. (2009)
The intrinsic viscosity of chitosan (MW 7.9 x 10(5) g mol(-1)) having a high degree of deacetylation and solubilised in aqueous formic and acetic acids was determined at room temperature. Contact angle and conductivity of the chitosan solutions were also studied. The values of critical coagulation concentration (CCC) were then obtained from the plots of contact angle or conductivity versus concentration.